Managerial forensics - Munoz, J. Mark.; Bivona, Diana Heeb. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Managerial forensics is the practice of gathering relevant corporate information for the purpose of analyzing and identifying reasons for managerial obstacles, mismanagement, bankruptcy, and corporate demise. This book assembles a cast of leading academic and business experts and shares their views on the best practices in corporate analysis. Following the notion that the past offers insights into the future, the book examines the maladies in contemporary business and offers strategies for corporate revival and turnaround.
Part I. Understanding managerial forensics -- 1. Introduction / J. Mark Munoz and Diana Heeb Bivona -- 2. From problem to cause / Diana Heeb Bivona -- 3. Featherston resources: a new, clean, green fertilizer business that failed / Sergio Biggemann and Alan Collier -- 4. Trust and legal considerations in managerial forensics / Zheng Liu and Alice de Jonge -- Part II. Tools in managerial forensics -- 5. Internal governance structures and corporate behavior / Alice de Jonge -- 6. Assessing leadership preparedness / Anthony Liberatore and J. Mark Munoz -- 7. Developing evidence-based data on ethics and culture / Duane Windsor -- 8. How to perform an autopsy on marketing strategy / Donald E. Sexton -- 9. Forensic accounting: show me the money / Scott P. McHone and Tricia-Ann Smith DaSilva -- 10. Forensic accounting for governmental entities / D. Larry Crumbley -- 11. Entrepreneurial forensics: assessing customers and decision makers in the biomedical field / Michael S. Kinch and Emre Toker -- 12. International forensics / J. Mark Munoz -- Part III. Strategies for corporate revival -- 13. Executive interview on managerial forensics: Keith Cooper, Senior Managing Director, FTI Finance and FTI Consulting / J. Mark Munoz -- 14. Team health: measuring it, understanding it, and improving it / Colin Price and Sharon Toye -- 15. Protecting value via information management / Al Naqvi -- 16. Changing direction / Diana Heeb Bivona -- Part IV. Conclusion -- 17. Conclusion / J. Mark Munoz and Diana Heeb Bivona -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on November 30, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Corporate turnarounds -- Management; Organizational change; Business analysts; business analysis; business consulting; business strategy; business turnaround; management analysis; management strategy; management turnaround; managerial forensics; organizational analysis; organizational development; Electronic books